A squandered opportunity: Even after the financial crisis, top positions in large financial firms still largely occupied by men - Elke Holst; Julia Schimeta (Weekly Report, 2011)
Despite the recent financial crisis and widespread mergers in the banking industry, the German financial sector remains largely unchanged in one respect: the percentage of women on the corporate boards of Germany's banks and insurance companies was nearly as low in 2010 as in the pre-crisis years. As a result, German companies have left the potential for innovation that has been shown to accompany a significant increase of women in top management untapped. Although more than half of all employees in the financial sector are women, only 2.9% of executive board members in Germany's major banks and savings institutions and just 2.5% of board members in the largest insurance companies are female. In this respect, the financial crisis has not changed the gender divide in top management. The percentage of women in board positions in Germany's largest 100 banks and savings institutions has remained almost constant since 2009; on the boards of German insurance companies, the percentage of women has even declined. Women are slightly better represented on supervisory boards than on executive boards: 16.3% of supervisory board members in the top 100 banks and savings institutions are female compared to just 11.9% in the top 62 insurance companies, a 0.5 point lower percentage than last year. The great majority of women were appointed to supervisory boards as employee representatives, thus as a result of co-determination legislation - 66.7% in the case of banks and savings institutions and 81.3% in the case of insurance companies. Moreover, public-sector banks are no models for gender equality in top management: with only 2% women on their executive boards and 16.5% on their supervisory boards, these state-run institutions are no better than their private-sector counterparts, despite federal and state gender equality legislation. However, the only women chairing supervisory boards in the public or private sector are found in public-sector banks and savings banks.
Keywords: G01; G3; J16; L32; M14; 330; financial sector; board diversity; women CEOs; gender equality; management; financial crisis